Aspek Rancangan Temperature Controller Room Storage Untuk Ayam Broiler Berbasis Internet Of Things (IOT) - Indra Septia Gunawan; Indra Yasri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Broiler chicken is a source of food that can be harvested within one month. The high level of feed consumption causes the body temperature of the chicken to heat up faster so that broiler chickens lose weight and even death. In the distribution of broiler chickens, broiler chicken storage is needed before being marketed, this storage has a problem that is hotter room temperature due to the chicken's own body heat and lack of air circulation. With a temperature controller, the risk of failure of broiler production can be handled. In this paper, an Internet of Things (IoT) system is created by reading and adjusting temperature conditions in broiler chicken storage. This design uses NodeMCU as a microcontroller with a built-in WIFI ESP8266 module, DHT11 sensor is used for temperature readings. The android application is designed using the Web-based MITAPPINVENTOR. This design will turn on the fan if the temperature in the storage exceeds 30 °C and turn off the fan if the storage temperature is below 30 °C. The results of broiler chickens with the IoT system have weight gain because the chickens are not getting hot compared to broilers without the Internet of Things (IoT) system which have weight loss and death. Broiler chickens have a stable body weight with the Internet of Things (IoT). Keywords : Broiler chicken, Internet of Things (IoT), NodeMCU, DHT11 ,Temperature, control Storage, android.